Jogos reduzidos e as ações técnico-táticas de jovens jogadores de futebol - Farias, Vinícius Martins (2018)
Small-sided games are commonly used in soccer both for training and preparation of high performance players, as well for learning and development of young soccer players. However there is still no consensus in the literature on which formats and field dimensions are best suited for young players from different age groups. Therefore, the present study aimed to: a) perform a literature review in order to identify the main factors that can influence the technical-tactical behaviors of young players in small-sided soccer games; and b) compare the results of individual technical actions of young soccer players in different game formats. The individual technical actions of 66 players from the under-13, under-15 and under-17 squads of a soccer club, between the 7x7, 9x9 and 11x11 game formats. The results showed more involvements with the ball in the 7x7 than in the 11x11 format in all age groups evaluated, besides differences in the frequencies of technical actions among game formats and age groups. In general, the results found in the present study and in the literature indicate that smaller game formats can provide more involvements with the ball and individual technical actions for youth soccer players.